Dangshen Erling Decoction Ameliorates Myocardial Hypertrophy via Inhibiting Myocardial Inflammation - Zhong, Yigang; Chen, Liuying; Li, Miaofu; Chen, Lian; Qian, Yufeng; Chen, Chaofeng; Wang, Yi; Xu, Yizhou (Frontiers in Pharmacology, 2022)
Myocardial hypertrophy plays an essential role in the structural remodeling of the heart and the progression to heart failure (HF). There is an urgent need to understand the mechanisms underlying cardiac hypertrophy and to develop treatments for early intervention. Dangshen Erling Decoction (DSELD) is a clinically used formula in Chinese medicine for treating coronary heart disease in patients with heart failure. However, the mechanism by which DSELD produce its cardioprotective effects remains largely unknown. This study explored the effects of DSELD on myocardial hypotrophy both in vitro and in vivo. In vitro studies indicated that DSELD significantly (P<0.05) reduced the cross-sectional area of the myocardium and reduced elevated LDH, TNF-α and IL-6 levels in the induced H9C2 cell model to study inflammation. In vivo experiments revealed that DSELD restores cardiac function, and significantly reduces myocardial fibrosis in isoproterenol (ISO)-induced HF mouse model (P<0.05). In addition, DSELD down-regulated the expression of several inflammatory cytokines, such as GM-CSF, G-CSF, IL-1α, IL-1β, IL-3, IL-5, IL-7, IL-12, IL-13, and TNF-α in HF (P<0.05). Further analysis of the cardiac tissue demonstrated that DSLED produces its anti-inflammatory effects via the Toll-like receptor-4 (TLR4) signaling pathway. The expression of TLR4 downstream proteins such as matrix metallo-protein-9 (MMP9) and myeloid differentiation factor-88 (MyD88) were among the regulated targets. In conclusion, these observations suggest that DSELD exerts anti-hypertrophic effects by alleviating the inflammatory injury via the TLR4 signaling pathway in HF and thus holds promising therapeutic potentials.